2020
DOI: 10.1002/ceat.202000056
|View full text |Cite
|
Sign up to set email alerts
|

Computational Analysis of the Solid‐State and Solvation Properties of Carbamazepine in Relation to its Polymorphism

Abstract: The solvent-dependent polymorphism of the active pharmaceutical ingredient (API) carbamazepine is interpreted from calculations of the solid-state and API-solvent intermolecular interactions. These simulations suggested that apolar solute-solute interactions could be disrupted by apolar solvents. In contrast, the polar solute-solute interactions were found to be easily disrupted by polar and protic solvents. This is consistent with experimental observations that the crystallization of the metastable form II is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 42 publications
0
1
0
2
Order By: Relevance
“…To understand the mechanism of stabilizing metastable form II by the phenyl-functionalized silica template, the crystal structures of forms II and III were discussed. In our previous study, the intermolecular interactions in forms III and II were calculated, as shown in Figure . The strongest interactions were found to be non-hydrogen bonding contacts, whose values were −9.8 and 10.6 kcal mol –1 in forms II and III, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…To understand the mechanism of stabilizing metastable form II by the phenyl-functionalized silica template, the crystal structures of forms II and III were discussed. In our previous study, the intermolecular interactions in forms III and II were calculated, as shown in Figure . The strongest interactions were found to be non-hydrogen bonding contacts, whose values were −9.8 and 10.6 kcal mol –1 in forms II and III, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Buscando informações adicionais em relação a estabilização da estrutura do H2L2f, causada pela interação entre os anéis pirazólicos e as interações supramoleculares do ligante com as moléculas de água de hidratação, realizou-se cálculos pelo método de campo de força ("force field") para avaliar as contribuições das energias de interações intermoleculares no empacotamento cristalino. Utilizou-se, através do programa Mercury 3.0, o componente "UNI Intermolecular Potentials" (MACRAE et al, 2020;GAVEZZOTTI, 1994;GAVEZZOTTI;FILIPPINI,1994;ROSBOTTOM;CHENG;HENG, 2020;LEE et al, 2019), presente no pacote "CSD-Materials".…”
Section: Simulação Computacional Por Dft Dos Espectros De Uv-vis Dos ...unclassified
“…As ligações intramoleculares discutidas acima são iguais as observadas para o composto H2L1a (PAVAN et al, 2010;BIKAS et al, 2012), indicando que a substituição do átomo de hidrogênio presente no anel fenil do H2L1a, pelo átomo de cloro retirador de elétrons do H2L2a (distância Cl(1)-C( 14 Seguindo o mesmo procedimento realizado com os ligantes de cadeia fechada (seção 4.2.1.1.1), foram obtidos valores das energias de interações intermoleculares presentes na rede cristalina das moléculas H2L1a e H2L2a, calculadas pelo método do campo de força através do componente "UNI Intermolecular Potentials", presente no pacote "CSD-Materials" do programa Mercury 3.0 (MACRAE et al, 2020;GAVEZZOTTI et al, 1994;GAVEZZOTTI;FILIPPINI, 1994;ROSBOTTOM;CHENG;HENG, 2020;LEE et al, 2019).…”
Section: Simulação Computacional Por Dft Dos Espectros De Uv-vis Dos ...unclassified